Sant, socit et politiqueen Afrique - Niang, Cheikh Ibrahima (Book collections on Project MUSE., 2008)
A re-conceptualisation of the health question and approaches based on the questioning of dominant paradigms are therefore needed to confront the on-going health crisis and put Africa on track for development.